Some introductory notes on the development and characteristics of Sabah Malay - Hoogervorst, Tom G. (UI Scholars Hub, 2011)
This is a preliminary description of the Malay variety used as a lingua franca in the Malaysian state of Sabah at the northernmost top of Borneo. The paper discusses a number of common linguistic features that distinguish Sabah Malay from other Malay varieties and analyses these features from a historical linguistic perspective. While it is argued that Sabah Malay has a close historical relation with other Malay dialects spoken in Borneo, especially Brunei Malay, the vernacular is also influenced phonologically and lexically by Sabah's indigenous and immigrant speech communities. Words and sentences recorded or elicited during fieldwork in various parts of Sabah illustrate these points.